3-D Rarities - Norling, Jack; MacLaren, Norman; Lambart, Evelyn; Ekman, Gretta; Crolius, Larry; Miner, Allen H.; Sprunck, Paul G.; Sparber, Isidore; Kneitel, Seymour (Flicker Alley, 2015)
It has taken over 30 years for the 3-D Film Archive to assemble and restore the material in 3-D Rarities, an eye-popping collection of ultra-rare and long-lost movies, which Flicker Alley and the 3-D Film Archive are proud to present here for the first time on Blu-ray. Selections include "Kelley's Plasticon Pictures", the earliest extant 3-D demonstration film from 1922 with incredible footage of Washington and New York City; "New Dimensions", the first domestic full color 3-D film originally shown at the World’s Fair in 1940; "Thrills for You", a promotional film for the Pennsylvania Railroad; "Around is Around", a 3-D animated gem by Norman McLaren; "Rocky Marciano vs. Jersey Joe Walcott", the only 3-D newsreel; "Stardust in Your Eyes", a hilarious standup routine by Slick Slavin; trailer for "The Maze", with fantastic production design by William Cameron Menzies; "Doom Town", a controversial anti-atomic testing film mysteriously pulled from release; puppet cartoon "The Adventures of Sam Space", presented in widescreen; "I’ll Sell My Shirt", a burlesque comedy unseen in 3-D for over 60 years; "Boo Moon", an excellent example of color stereoscopic animation … and more! [www.flickeralley.com]
Keywords: DVD-Video